Physical Activities with the Event of Dementia in the Elderly at Tresna Werdha Social Original Hutuo Beringin - Rona Febriyona; Nur Uyuun I. Biahimo; Fahmi Lihu (PSPP JOURNALS, 2022)
The aging process in the elderly is accompanied by a decrease in physical conditions that can inhibit the elderly in doing physical activity, as a result of which the elderly are at risk of developing dementia. The purpose of this study was to find out the relationship of physical activity with the incidence of dementia in the elderly at the Tresna Werdha Beringin Hutuo Social Home. Cross sectional study design, the population of all the elderly in Tresna Werdha Beringin Hutuo Social Home as many as 43 elderly. The sample numbered 43 elderly using the Total Sampling technique. The instruments used were a GPAQ questionnaire to measure physical activity and an MMSE questionnaire to measure the incidence of dementia and using chi-square statistical tests. The results obtained there is a relationship of physical activity with the incidence of dementia in the elderly in Tresna Werdha Beringin Hutuo Social Home with a value of p-value 0.006. Thus, it can socialize to the elderly to do physical activity and plan and implement a program of activities.